Multi-scale drivers of microbial biodiversity across small water bodies in northern regions - Teittinen, Anette (Helsingin yliopisto, 2019)
The patterns and drivers of microbial biodiversity remain less described and understood than those of larger organisms. Considerable knowledge gaps regarding microorganisms remain especially among small water bodies, which contribute significantly to biodiversity across northern landscapes. The main aims of this thesis were (1) to investigate microbial biodiversity patterns and multi-scale drivers along elevational gradients in subarctic streams and ponds; (2) to explore the effects of species niche characteristics and traits on elevational distributions of pond diatoms; (3) to test for the theory of island biogeography and to identify the factors affecting diatom biodiversity in boreal springs; and (4) to investigate the factors shaping diatom biodiversity along a land-use intensity gradient across boreal streams. To achieve these aims, small streams, ponds, and springs in the boreal and subarctic regions were sampled for microorganisms, and a variety of explanatory variables representing local environmental conditions, catchment properties and climatic and spatial factors were measured or derived from existing databases. The studied microbial groups comprised diatoms, cyanobacteria, and non-cyanobacteria (i.e., bacteria other than cyanobacteria). To examine the relationships between microbial biodiversity and explanatory variables, advanced statistical methods were used. The results showed that in the subarctic streams, diatom species richness or range size exhibited no consistent elevational patterns, whereas community similarity decreased primarily with elevational distance. Diatom communities among the streams were shaped by local-scale variables, such as water depth, and regional drivers, including dispersal and geographical factors. In the subarctic ponds, the richness–elevation relationship was unimodal for diatoms and cyanobacteria, whereas non-cyanobacteria richness declined with increasing elevation. Ponds at both ends of the elevational gradient harboured taxonomically unique microbial communities. ...